Komunikasi dalam Pengambilan Keputusan Ekonomi di Kalangan Keluarga Sasaran Program CSR di Jatigede Timur - Agus Rahmat; Mansyur Mansyur; Dian Wardiana Sjuchro; Rina Fitriana (Society, 2025)
At the micro or local level, many Corporate Social Responsibility (CSR) programs are beneficial to communities. Most CSR initiatives focus on the economic aspect through income-generating activities. Previous researchers have extensively discussed the implementation processes and benefits of CSR programs for communities. However, a common challenge in the implementation of these programs is the difficulty faced by organizers in engaging target groups, due to factors such as family communication and internal references. This issue has attracted researchers to explore how communication influences decision-making regarding participation among beneficiaries or target groups of CSR programs, particularly in ensuring that the economic objectives set for target families can be successfully achieved. This study employs a qualitative method, utilizing structured interviews and focus group discussions (FGDs) involving 120 informants from CSR target groups considered representative. The findings indicate that the head of the household, as the primary target of the CSR program, communicates with his spouse and extended family when making decisions. The involvement of individuals outside the extended family is based on considerations of trust. The outcomes of these communication processes—among the head of the family, spouse, extended family, and trusted individuals—are significant in shaping a family’s decision to participate in a CSR program. Understanding who serves as a source of influence and inspiration in encouraging families to engage in CSR activities can enhance participation and interest among target communities, ultimately contributing to the success of the program.